Perspective chapter: the interactive perspective in social media usage studies - Nie, Zhou; Waheed, Moniza; Kasimon, Diyana; Wan Abas, Wan Anita (IntechOpen Limited, 2024)
Social media usage is heavily influenced by individual interactions, as supported by empirical research. These interactions shape the cultural and social contexts of social media, resulting in diverse usage behaviors. Social media’s ability to transcend temporal and spatial barriers amplifies this dynamic. Interactions are fundamental to understanding social media as a systematic behavior occurring in both micro and macro systems, serving dual purposes of maintaining equilibrium and facilitating changes. They help systems achieve collective goals beyond individual capacities while also enabling necessary changes to adapt to the external environment. Thus, systematic research method, particularly employing social network analysis, is crucial for understanding human interactions in social media usage. For that social network analysis focuses on the formation and changes of structures formed by interactions. Integrating social network analysis into research can lead to a paradigm shift toward a more systematic perspective in social media research. This study aims to accomplish this by formulating hypotheses through an extensive literature review, aiming to inspire more empirical studies in the realm of social media usage.